A viviparous brackish-water ampharetid, Alkmaria romijni Horst from Ringkøbing Fjord - Wesenberg-Lund, Elise (Videnskabelige Meddelelser fra Dansk naturhistorisk Forening i Köbenhavn Forening, 1934)
None
World Polychaeta Database (WPolyDb). Species name in title was formerly misspelled in the WoRMS entry, corrected August 2015